2021
DOI: 10.3390/vaccines9091013
|View full text |Cite
|
Sign up to set email alerts
|

Varicella Zoster Virus Reactivation Following COVID-19 Vaccination: A Systematic Review of Case Reports

Abstract: The newly developed COVID-19 vaccines have established a safe profile, yet some individuals experience a wide range of adverse events. Recently, reactivation of varicella zoster virus (VZV) has been observed after administration of different COVID-19 vaccines, although causality remains a matter of debate. The aim of this systematic review was to examine the available literature and provide an overview of reported cases of VZV reactivation following COVID-19 vaccination. We identified 12 eligible articles whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(141 citation statements)
references
References 40 publications
6
133
2
Order By: Relevance
“…A systematic review described 91 patients with HZ following COVID-19 vaccination. Important comorbidities in these patients included hypertension, autoimmune disorders, and immunosuppression [85]. In a recent narrative review on HZ after COVID-19 vaccination by Iwanaga, et al, 399 cases are reported.…”
Section: Vzv Reactivation and Covid-19mentioning
confidence: 99%
“…A systematic review described 91 patients with HZ following COVID-19 vaccination. Important comorbidities in these patients included hypertension, autoimmune disorders, and immunosuppression [85]. In a recent narrative review on HZ after COVID-19 vaccination by Iwanaga, et al, 399 cases are reported.…”
Section: Vzv Reactivation and Covid-19mentioning
confidence: 99%
“…All of them developed symptoms of VZV reactivation after 5.8 days of vaccination. Valacyclovir oral administration was used for treatment (Triantafyllidis et al 2021 ).…”
Section: Rare Adverse Effects Of Covid-19 Vaccines (Refer To Table 9 )mentioning
confidence: 99%
“…2 Similar findings were reported in other studies 3 and herpes zoster was more common in patients receiving mRNA vaccines. 4 The possible hypothesis proposes that COVID-19 mRNA or vaccine adjuvants enhance strong T-cell responses 5 while compromising VZV-specific CD8+ T-cell immunity. In addition, vaccine mRNA or nanoparticle envelope may enhance the cytokines such as the type 1 interferons via Toll-like receptors signalling.…”
Section: Herpes Zoster Reactivation After Mrna-1273 Vaccination In Patients With Rheumatic Diseasesmentioning
confidence: 99%